2021
DOI: 10.1038/s41598-021-87532-0
|View full text |Cite
|
Sign up to set email alerts
|

A model of processive walking and slipping of kinesin-8 molecular motors

Abstract: Kinesin-8 molecular motor can move with superprocessivity on microtubules towards the plus end by hydrolyzing ATP molecules, depolymerizing microtubules. The available single molecule data for yeast kinesin-8 (Kip3) motor showed that its superprocessive movement is frequently interrupted by brief stick–slip motion. Here, a model is presented for the chemomechanical coupling of the kinesin-8 motor. On the basis of the model, the dynamics of Kip3 motor is studied analytically. The analytical results reproduce qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In time t r , the binding energy of the ADP-head to the local α/β-tubulin changes from E w1 to E w2 . As shown elsewhere, based on the above deduction, the proposed Brownian dynamics model for the chemomechanical coupling of kinesin dimers can explain well various experimental data on dynamics of different families of N-terminal kinesin motors such as kinesin-1, kinesin-3, kinesin-5, kinesin-8, and orphan kinesin PAKRP2 [28][29][30][31][32][33]. In particular, to fit the available single molecule data on load dependences of velocity, dissociation rate, run length, etc., for the kinesin motors, using the proposed Brownian dynamics model, it was estimated that E w1 ≤ 25 k B T and E w2 ≥ 35 k B T [30,[33][34][35][36][37][38], which are consistent with the values of E w1 = 17.7 k B T and E w2 = 35 k B T calculated here using all-atom MD simulations.…”
Section: Discussionsupporting
confidence: 55%
“…In time t r , the binding energy of the ADP-head to the local α/β-tubulin changes from E w1 to E w2 . As shown elsewhere, based on the above deduction, the proposed Brownian dynamics model for the chemomechanical coupling of kinesin dimers can explain well various experimental data on dynamics of different families of N-terminal kinesin motors such as kinesin-1, kinesin-3, kinesin-5, kinesin-8, and orphan kinesin PAKRP2 [28][29][30][31][32][33]. In particular, to fit the available single molecule data on load dependences of velocity, dissociation rate, run length, etc., for the kinesin motors, using the proposed Brownian dynamics model, it was estimated that E w1 ≤ 25 k B T and E w2 ≥ 35 k B T [30,[33][34][35][36][37][38], which are consistent with the values of E w1 = 17.7 k B T and E w2 = 35 k B T calculated here using all-atom MD simulations.…”
Section: Discussionsupporting
confidence: 55%
“…Mechanical analysis indicates that as kinesin walks on the microtubule surface, it can carry a load of up to 6–8 pN. 35 In mechanical separation experiments of DNA, it was found that the force required to pull apart the double helix of a DNA molecule is ∼100 pN. 36 However, the electric forces generated by TTFields on MT, KT plate, and kinesin heads are notably smaller than the intrinsic typical values, indeed, smaller by an order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the previous argument for the potential form of the kinesin-1 head interacting with MT in the theoretical and numerical studies. [63,64]…”
Section: Dissociation Along the Forward Directionmentioning
confidence: 99%